Myth, fantasy and magic in Gente del mundo, by Alberto Chimal - Pérez-Amezcua, Luis Alberto; Sigala Gómez, Ricardo (Amaltea. Revista de Mitocrítica, 2018)
This article explores the way in which Mexican writer Alberto Chimal uses the sermo mythicus in his book Gente del mundo to practice a fantastic literature or an imagination literature that appeals to mythological memory. It is concluded that such a literary strategy as the one of the usage of a symbolic field strategically and intimately related with that sermo result both effective for the establishment, in the text, of a restorative mythopoetic statute in contemporary society.